The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph19073827
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of Diabetic Foot Ulcer Care during the First Year of the Pandemic in Poland: A Retrospective National Cohort Study

Abstract: The COVID-19 pandemic revealed a breakdown of the system of DFU patient care. This retrospective national cohort study analyses the epidemiological status of DFU patients in relation to urgent and elective hospitalizations, amputation rates, and deaths in Poland from 2017 to 2019, and during 2020 when the COVID-19 pandemic began. The data were obtained from national medical records gathered by the National Health Fund (NHF). Discharge diagnoses were categorized according to ICD-10 and ICD-9 codes. Analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 53 publications
(72 reference statements)
3
11
1
2
Order By: Relevance
“…In Poland, Kleibert et al [ 45 ] reported an increase in the total number of DFU amputations compared to the pre-COVID era. In particular, the authors did not observe a decrease in the number of majors amputations (above the knee) and simultaneously an increase in minor amputations (below the ankle).…”
Section: The Indirect Impact Of the Covid-19 Pandemic On Diabetes-rel...mentioning
confidence: 99%
See 2 more Smart Citations
“…In Poland, Kleibert et al [ 45 ] reported an increase in the total number of DFU amputations compared to the pre-COVID era. In particular, the authors did not observe a decrease in the number of majors amputations (above the knee) and simultaneously an increase in minor amputations (below the ankle).…”
Section: The Indirect Impact Of the Covid-19 Pandemic On Diabetes-rel...mentioning
confidence: 99%
“…The first reports during the lockdown were limited to small cohorts of single specialized centers which showed different results [24,39,40,43,[47][48][49][50][51][52], while subsequently several complete population studies have been published [42,[44][45][46]56].…”
Section: Conclusion and Lessons Learned For Our Futurementioning
confidence: 99%
See 1 more Smart Citation
“…This characteristic of our study was also harmonious with the literature. [4][5][6] During the pandemic period, more people who required any level of amputation had end-stage renal disease and vascular disease. This difference may be a result of lacking analyses and physical examination in telemedicine settings.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic posed major challenges in DFU care across the globe due the above reasons[ 9 - 11 ]. Delays in ulcer reviews may be associated with detrimental effects on DFU healing that may even lead to amputations[ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%